Memento: Coordinated Caching for Data-Intensive Clusters - Ananthanarayanan, Ganesh; Ghodsi, Ali; Shenker, Scott; Stoica, Ion (2011)
11:30-11:50, Paper ThB5.4 Add to My Program Memento: Coordinated Caching for Data-Intensive Clusters (I) Ananthanarayanan, Ganesh UC Berkeley Ghodsi, Ali UC Berkeley Shenker, Scott UC Berkeley Stoica, Ion UC Berkeley
Allerton Conference [Invited Paper]